The origin and theological content of the Litany of the Most Holy Name of Jesus - Kwiatkowski, Dariusz (Poznańskie Studia Teologiczne, 2018)
The article presents the sources, origin and theology of the Litany to the Holy Name of Jesus. The rst part shows the mystery of names. It is the symbolism of man and the process of mutual communication that is the core. Names are the living souls of every being. Thanks to names, human beings are not anonymous. In ancient times, names would never be overlooked as insigni cant conventional terms as they had a meaningful part in the role that a given being took on in the uni- verse. The name has a meaning and is treated as a kind of a spiritual substance, as something real, something that truly exists. The sources of Jesus’ titles present in the Litany to the Name of Jesus are the Holy Scriptures, the writings of the Fathers of the Church and popular piety. The Litany to the Holy Name of Jesus shows the richness of the content in the Name of Jesus, which contains the truth about His deity and His in nite love for the whole of creation and especially for every human being. The Litany is a summary of the entire history of salvation, in which the name of Jesus became “a name above all names” (see Flp 2: 8-11).